Assessment of the technical acceptability of innovative construction products: environmental and economic parameters and requirements - Skakun, V.; Halunka, O.; Kazmin, O. (Ways to Improve Construction Efficiency, 2023)
The article examines the process of assessing the technical acceptability of construction products that embody innovative properties. The evaluation procedure for such products should be carried out on a dual scale – taking into account both environmental and economic parameters to ensure a full understanding of the viability of the product. The environmental parameters and environmental impact considered in the assessment cover a range of factors, including life cycle assessment (LCA), carbon footprint and adherence to circular economy principles. There is especially little assessment of the life cycle flow of a building, after which life cycle pricing provides a holistic detection, assessing the complex impact of building products on the environment. Carbon considerations focus on the total carbon emissions associated with production, transportation and installation, which contribute to broader sustainability goals. The principles of the circular economy guide the evaluation towards more efficient use of resources and reduction of waste, emphasizing the importance of recyclability and durability. At the same time, the player’s economic parameters provide a key role in determining the technical acceptability of innovative construction products. Economic viability is assessed through factors such as economic efficiency, life cycle cost and overall economic sustainability. The assessment covers the long-term economic prospects and demonstration economics associated with innovative products, ensuring their feasibility within the economic constraints of construction projects. The study emphasizes the relationship between environmental and economic parameters, notes that technical acceptability has the effect of not only technical and environmental constraints, but requires a balanced assessment of all dimensions. The integration of these parameters is consistent with the industry’s broader transition to sustainable and economically viable construction methods. Outlines requirements for technical acceptability, emphasizing the need for validation of regulatory standards, certification and transparent documentation, using an integrated approach involving stakeholders, industry experts and regulatory bodies to reach consensus on technical acceptability criteria for innovative construction products, contains a detailed study of technical acceptability assessment, recognizing the key role played by environmental and economic parameters. Incorporating both dimensions, the evaluation system seeks to recognize acceptable innovative construction products that not only meet technical standards, but also promote sustainable and economically viable construction practices.